Effect of Supplementing Feed with Kepok Banana Peel Extract (Musa balbisiana Colla) on the Growth and Survival Rate of Nile Tilapia (Oreochromis niloticus) Fry - Nur Putih Rahmatillah; Emmy Syafitri; Dwi Tika Afriani (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of kepok banana peel extract (Musa balbisiana Colla) as a feed additive on the growth and survival of Nile tilapia (Oreochromis niloticus) fry, as well as to identify the optimum dosage. The study was motivated by the high cost of feed and the underutilization of agricultural waste as a functional feed ingredient. An experimental method employing a completely randomized design (CRD) was used, consisting of four treatments and three replicates: feed without extract (control) and feed supplemented with kepok banana peel extract at doses of 150, 200, and 250 g/kg feed. The experiment involved 12 experimental units stocked with Nile tilapia fry with an initial average size of ±3 cm and reared for 28 days. The observed parameters included absolute weight gain, absolute length gain, and survival rate. Data were analyzed using analysis of variance (ANOVA), followed by the least significant difference (LSD) test at the 5% significance level. The results showed that supplementation with kepok banana peel extract had a highly significant effect (P<0.01), indicating that the treatments produced statistically significant differences at a 99% confidence level. Further analysis revealed that each treatment differed significantly, with growth increasing in line with increasing extract dosage. The treatment at a dose of 25% per kg feed produced the highest growth, with an absolute weight gain of 5.43 g, an absolute length gain of 4.43 cm, and a survival rate of 86.6%. Water quality remained within the optimal range throughout the study. These findings indicate that kepok banana peel extract has potential as a natural feed additive that supports waste utilization and the sustainability of Nile tilapia aquaculture.